Synthesis, characterization and electrical properties of novel mono- and cofacial bisphthalocyanines bridged with four [1a,8b-dihydronaphtho[b]naphthofuro[3,2-d]furan-7,10-diyl] units - ODABAŞ, ZAFER (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Novel mono phthalocyanines and cofacial bisphthalocyanines were synthesized from 4,4 '-(1a,8b-dihydronaphtho[b]naphthofuro-[3,2-d]furan-7,10-diyl)bis(oxy)diphthalonitrile 1. The products were characterized by elemental analysis, UV-vis, IR, 1H NNIR and mass spectroscopy. Both the direct current (dc) and alternatin current (ac) electrical properties of the product films were investigated as a function of temperature in the frequency range 40-10(5) Hz. It was observed that the ac response of the films can be represented by the omega(s) law. The temperature dependence of dc conductivity showed typical Arrhenius behavior for all compounds. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: SANDWICH DILUTETIUM TETRAPHTHALOCYANINE; GAS-SENSING PROPERTIES; BINUCLEAR PHTHALOCYANINES; ELECTROCHEMICAL PROPERTIES; CIRCULAR-DICHROISM; METAL-FREE; COMPLEXES; ZINC(II); SPECTROELECTROCHEMISTRY; METALLOPHTHALOCYANINES